Comparison of glacier velocity maps determined over Axel Heiberg Island, Canadian high Arctic derived from differing SAR sensors - Samo, Lauren; van Wychen, Wesley; Wendleder, Anna; Copland, Luke; Thompson, Laura (2022)
Rates of atmospheric warming in the Canadian Arctic (CA) are twice the global average and are impacting glacier behavior: causing longer and more intense melt seasons; modifying glacier motion; and leading to persistent glacier mass loss. This study aims to further understand the impact of this warming through the investigation of a decadal record of glacier velocities for Thompson and White Glaciers (Axel Heiberg Island) in the CA. This study creates a dense time series of glacier motion from 2008-2020, by applying an offset tracking algorithm to data acquired by two different SAR sensors: RADARSAT-2 (R2) and TerraSAR-X (TSX). Openly available velocity maps, that are pre-derived from Sentinel-1 (S1) SAR imagery, are also used to augment the record we have created. A comparison of the glacier velocity maps produced from each of these sensors indicates that the TSX data provides more velocity maps with lower error than both R2 and S1 data, both of which contain more variability due to noise. Over non-moving bedrock outcrops, initial tests indicate that TSX data provide an overall error of 3.74 m yr-1 with a standard deviation of 2.39 for the period of March 2020. Over the same period and spatial area, pre-derived S1 products yielded an overall error of 9.81 m yr-1 with a standard deviation of 7.45. Previous studies that have utilized R2 data, provided an error of 4.81 m yr-1 and a standard deviation of 3.15 for the ice caps on AHI for 2019-2020. We suggest that the TSX results are likely due to shorter temporal resolution of an 11 day repeat pass compared to 24 days for R2. S1 has either a 6 or 12 day repeat pass but poorer resolution of the data likely that degrades the velocity results. Differing image pixel resolutions could be another cause of improved results from TSX data. To further characterize and constrain the uncertainty of each of these datasets, all the SAR based velocities are compared with in situ dGPS observation for White Glacier. Overall, this work ‘rescues’ a large catalogue of SAR imagery ...